Flexible organic field-effect transistors with high-reliability gate insulators prepared by a room-temperature, electrochemical-oxidation process. Issue 20 (6th March 2015) - Sun, Sheng; Lan, Linfeng; Xiao, Peng; Lin, Zhenguo; Xu, Hua; Xu, Miao; Peng, Junbiao
<x xml:space="preserve">Abstract</x> Flexible OFETs with electrochemically oxidized gate insulators (AlOx:Nd) covered by a thin layer of Cytop were fabricated on a PEN substrate. The device exhibited higher mobility and better electrical stability.